Clear it with Sid! : Sidney R. Yates and fifty years of presidents, pragmatism, and public service - Dorf, Michael C.; Van Dusen, George (University of Illinois Press, 2019)
"From 1949 to 1999, Congressman Sidney R. Yates of Illinois served under ten Presidents of the United States and eight Speakers of the House of Representatives. He debated and helped shape many of the major issues which formed America's dominance of the postwar world. In particular, as an Appropriations Subcommittee Chairman, a member of the 'College of Cardinals,' Yates became the preeminent legislator on the environment, Native American rights, human rights, Israel and anti-Semitism, and the arts and humanities. As Speaker Tip O'Neill would tell congressmen when sensitive policy questions arose, 'Clear it with Sid!' In 'Clear it With Sid,' Michael C. Dorf and George Van Dusen trace the evolution of Sid Yates, son of a blacksmith from Lithuania, from freshman congressman to venerated elder statesman and recipient of the Presidential Citizens Medal. With unprecedented access to the papers, family, and friends of Yates, they round out the portrait of a man who could be petty and stubborn at times, but who had also found the key to being effective, respected, and able to reach across a violently partisan aisle, demonstrating that even in these hostile times, there are ways for representatives to work together for the public good"--